Queer animation: a creative project in constructing fantastical worlds of desire - Del Castello, Daniel (My University, 2017)
The aim of the research report is to establish a link between the field/practice of queer theory and the field/practice of animation. I propose that the linking factor between these two bodies of theory and practice is fantasy. the purpose of exploring this link s to understand how formal elements of the animated medium can be used to articulate queer scenarios of desire: [Abbreviated Abstract. Open document to view full version]
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Art (Digital Art), September 2017
Keywords: Homosexuality and motion pictures; Homosexuality in motion pictures; Queer theory; Computer art